STUDI KOMPARASI KURIKULUM BAHASA ARAB TINGKAT SATUAN PENDIDIKAN DAN KURIKULUM 2013 SATUAN PENDIDIKAN DAN KURIKULUM 2013 (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2015)
This paper aims to find out the similarities and differencescontained in the KTSP and the 2013 curriculum Arabic subjectsMadrasah Aliyah from the aspect of goals, materials and methods. As well as knowingadvantages and disadvantages of both curriculum. Types of researchthis is a library research with a qualitative approach. Analysisthe data uses content analysis. Based on analysisconcluded that in the KTSP and the 2013 Arabic Curriculumfor Madrasah Aliyah, it has many similarities in aspects of purpose,material or method. It's just that the 2013 curriculum tries to complement itdeficiencies in KTSP as in the subject matter,the 2013 curriculum is more detailed in describing the scope of the material inin the form of KI and KD, besides that the 2013 curriculum does not only emphasizecognitive aspects only, but cognitive, psychomotor and affective aspectsbalanced and integrated into all subjects. Addition tothat, if in the KTSP the learning approach used varies,then the 2013 curriculum uses a scientific approach.